ANALISIS KEAKTIFAN DAN PEMAHAMAN SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE PADA MATERI PERUBAHAN WUJUD BENDA DI KELAS IV SD - RAHMA AYUNI; KMA FAUZI (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2026)
This study aimed to examine the implementation of the Think Pair Share (TPS) learning model in improving student participation and conceptual understanding of changes in the states of matter among fourth-grade elementary school students. The TPS model was selected because it encourages independent thinking, peer collaboration, and active communication during learning activities. This research employed a descriptive qualitative approach involving 18 fourth-grade students at UPTD SDN 010106 Sei Silau Barat. Data were collected through observation, interviews, documentation, and learning assessments. The novelty of this study lies in analyzing the contribution of each TPS stage (Think, Pair, Share) to student engagement and conceptual understanding in science learning. The findings showed an increase in student participation, with 14 students actively engaged in pair discussions and 12 students confidently presenting their results during class sharing sessions. In addition, 83.3% of students achieved scores above the minimum mastery criterion with an average score of 78.6. These results indicate that the TPS model effectively supports active, collaborative, and meaningful science learning at the elementary level.